Effect of rumen-protected choline supplementation on production performance and haemato-biochemical profile of Kankrej cows - Pawar, Mahesh M; Patil, Shrikant S; Panchasara, Harshad H; Patel, Jayveer R; Ahuja, Love C; Raut, Akash S; Modi, Chetna P; Gupta, Jay Prakash (Indian Journal of Dairy Science, 2023)
The peripartum period is critical for productivity, reproduction and health of dairy cows due to higher demands for nutrients and lower feed intake. A study was conducted to examine the effect of supplementation of rumen-protected choline chloride (RPC) on production performance and haemato-biochemical parameters of Kankrej cows. Twenty Kankrej cows were randomly allocated to two treatment groups: control (CON: fed basal diet without supplement) and treatment (RPC: basal diet supplemented with 50 g/d/cow of RPC) from 4-weeks pre-partum through 8-weeks post-partum. Results showed that average body weights and dry matter intake were not affected (P